1939 World's Fair Cake by Bill Baker, Ojai California (Curt Teich & Co., Inc.)
A presentation to the Golden Gate International Exposition in honor of the Baking Industry. Made from California products only and from the same recipe as the cake sent from California to President and Mrs. Roosevelt each Christmas. The decorations, made entirely of sugar and certified pure food coloring took one year to make. the dimensions of the cake: 5 feet on the base, 3 feet high and 3 feet across on top of the cake.